The Effect of Islamic Mental Health Psychoeducation as an Effort to Improve Mental Health Literacy in Adolescents - Norhayatun, Norhayatun; Musfichin, Musfichin; Mulyani, Mulyani (Indonesian Academy of Social and Religious Research (IASRR), 2023)
The lack of public understanding of mental health creates a negative stigma in society, leading to delays and inadequate treatment in addressing mental disorders. Therefore, this study aims to enhance mental health literacy among adolescents by providing Islamic mental health psychoeducation training. The research subjects were 11 students from Class XI Religion, MAN 1 Banjarmasin, utilizing a pre-experimental research design known as the one-group pretest-posttest design. The measurement tool used was the Islamic mental health literacy scale, and data analysis was conducted using a paired sample t-test. The results of this study indicated a significant difference between the pre-and post-intervention phases, as evidenced by the obtained hypothesis of p < 0.000 (p < 0.05). In conclusion, this research highlights the importance of providing Islamic mental health psychoeducation to improve mental health literacy among adolescents.